Quality Control of Tofu Production Processes Using the Seven Tools Method: Pengendalian Kualitas Proses Produksi Tahu Dengan Menggunakan Metode Seven Tools - Alwi, Mohammad Kharis; Cahyana, Atikha Sidhi (Universitas Muhammadiyah Sidoarjo, 2023)
Tofu is a food derived from soybeans which is then fermented to extract its juice. The problem that often occurs in the tofu industry is that the products produced still have a lot of defects. The purpose of this research is to identify the types of defects in tofu production and the causes of defects in tofu products and to improve product quality. The method used in this study is the seven tools method. Seven tools are 7 (seven) basic tools used to solve problems in production. The results of the research in the production process of SB tofu occurred 4 types of defects, namely defects in unequal size, defects in terms of texture, defects mixed with dirt and defects in color. The most dominant type of tofu SB defect is the type of size defect that is not the same with a percentage of 45.6%. This type of defect is caused by human, machine, material, method, and environmental factors.